KINERJA MARSHALL CAMPURAN LASTON DENGAN AGREGAT BULAT DARI SUNGAI KAMPAR SEBAGAI AGREGAT KASAR - Leo Sentosa; Elianora -; Linda Erly (Jurnal APTEK, 2010)
Terms of coarse aggregate to blend the mix of which is shaped kubikal, a plane of rupture of at least two and a rough surface texture, generally in the form of crushed stone, so that granular aggregate have a good interloking in the mix. However, in certain areas of aggregate supply that meets these requirements, sometimes difficult and requires a high cost. Especially in Riau Mainland, crushed stone aggregate shall be imported from Riau Kepuluan (Tanjung Pinang). Meanwhile, the Riau mainland itself has a considerable potential source of material derived from the Kampar River, but it is round and smooth surface texture.